Cangrelor alleviates bleomycin-induced pulmonary fibrosis by inhibiting platelet activation in mice. (April 2020) - Zhan, Tianwei; Wei, Taofeng; Dong, Lingjun; Wang, Qi; Wu, Zixiang; Yan, Qihang; Zhang, Weiping; Lu, Yunbi; Wu, Ming
Highlights: Cangrelor mitigated lung fibrosis may partly through the inhibition of platelets. Platelet activtion, neutrophils infiltration and cytokine expression were suppressed by cangrelor treatment in mice. Cangrelor could be a potential therapeutic drug for pulmonary fibrosis. Abstract: Pulmonary fibrosis is a progressive chronic inflammatory lung disease whose pathogenesis is complicated. Platelets and neutrophils play important roles in the progression of pulmonary inflammation. We have reported that cangrelor, a non-sepesific GPR17 antagonist, alleviates pulmonary fibrosis partly by inhibiting macrophage inflammation in mice. Cangrelor is also a well-known anti-platelet agent. To test whether cangrelor mitigated pulmonary fibrosis partly through the inhibition of platelets, bleomycin (BLM) was used to induce pulmonary fibrosis in C57BL/6 J mice. We found that cangrelor (10 mg/kg) not only significantly decreased BLM-induced release of inflammatory cytokines (PF4, CD40 L and MPO), but also decreased the increment of platelets, neutrophils and platelet-neutrophil aggregates in the fibrotic lung and in the peripheral blood of BLM-treated mice. In addition, cangrelor decreased the number of CD40 and MPO double positive neutrophils and the expression level of CD40 in BLM-treated mouse lungs. Based on these results we conclude that cangrelor alleviates BLM-induced lung inflammation and pulmonary fibrosis in mice, partly through inhibition of platelet activation, therefore reducing the infiltration of neutrophils due to the adhesion of platelets and neutrophils mediated by CD40 - CD40 L interaction. Cangrelor could be a potential therapeutic medicine for pulmonary fibrosis.